Resiprositas Multi Pihak dalam Pelaksanaan Akses Reform untuk Membangun Kesejahteraan Masyarakat di Kabupaten Batang, Provinsi Jawa Tengah - Nugroho, Aristiono; Sari, Dian Mardiati; Moha, Devie Indriany (Indonesian Journal of Computer Science and Engineering, 2025)
Batang Regency, Central Java Province has several physical and non-physical potentials that can be utilized in the form of reform access, especially in Tumbrep Village and Surjo Village, which consist of creating conditions and implementing reform access, where the form of multi-party reciprocity in implementing reform access consists of various supports, such as: (1) resource support, (2) knowledge support, (3) training support, (4) management support, and (5) marketing support. However, in multi-party reciprocity in implementing reform access, there are obstacles that are faced, namely: (1) Complexity of management, consisting of fund allocation, coordination between various institutions, and monitoring of impacts, (2) Complexity of coordination, which causes: overlapping programs, and unclear roles and responsibilities of each party, (3) inequality of power, for example the relationship between: government and society, private sector and society, BUMD and society, and NGOs and society